Mast cells expedite control of pulmonary murine cytomegalovirus infection by enhancing the recruitment of protective CD8 T cells to the lungs. - Stefan Ebert; Marc Becker; Niels A W Lemmermann; Julia K Büttner; Anastasija Michel; Christian Taube; Jürgen Podlech; Verena Böhm; Kirsten Freitag; Doris Thomas; Rafaela Holtappels; Matthias J Reddehase; et al. (PLoS Pathogens, 2014)
The lungs are a noted predilection site of acute, latent, and reactivated cytomegalovirus (CMV) infections. Interstitial pneumonia is the most dreaded manifestation of CMV disease in the immunocompromised host, whereas in the immunocompetent host lung-infiltrating CD8 T cells confine the infection in nodular inflammatory foci and prevent viral pathology. By using murine CMV infection as a model, we provide evidence for a critical role of mast cells (MC) in the recruitment of protective CD8 T cells to the lungs. Systemic infection triggered degranulation selectively in infected MC. The viral activation of MC was associated with a wave of CC chemokine ligand 5 (CCL5) in the serum of C57BL/6 mice that was MC-derived as verified by infection of MC-deficient Kit(W-sh/W-sh) "sash" mutants. In these mutants, CD8 T cells were recruited less efficiently to the lungs, correlating with enhanced viral replication and delayed virus clearance. A causative role for MC was verified by MC reconstitution of "sash" mice restoring both, efficient CD8 T-cell recruitment and infection control. These results reveal a novel crosstalk axis between innate and adaptive immune defense against CMV, and identify MC as a hitherto unconsidered player in the immune surveillance at a relevant site of CMV disease.